Reducing anxiety and enhancing physical performance by using an advanced version of EMDR: a pilot study. Issue 3 (12th February 2014) - Rathschlag, Marco; Memmert, Daniel
Abstract Background The main aim of this pilot study was to investigate an advanced version of eye movement desensitization and reprocessing (EMDR) for reducing anxiety. Methods Fifty participants were asked at two times of measurement (T1 and T2 with a rest of 4 weeks) to generate anxiety via the recall of autobiographical memories according to their anxiety. Furthermore, the participants were randomly assigned to an experimental group and a control group, and the experimental group received an intervention of 1–2 h with the advanced version of EMDR in order to their anxiety 2 weeks after T1. At T1 as well as T2, we measured the intensity of participants' anxiety with a Likert scale (LS) and collected participants' state (temporary) and trait (chronic) anxiety with the State‐Trait Anxiety Inventory (STAI). In addition, we measured participants' physical performance in a test for the finger musculature under the induction of their anxiety. Results The results showed that participant's ratings of their perceived intensity of anxiety (measured by a 9‐point LS) and the state and trait anxiety decreased significantly in the experimental group but not in the control group from T1 to T2. Moreover, the physical performance under the induction of participants' anxiety increased significantly in the experimental group from T1 to T2 and there were no significant changes in the control group. Conclusions The study could show that the advanced version of EMDR is an appropriate method to reduce anxiety.